1978
DOI: 10.1083/jcb.77.3.805
|View full text |Cite
|
Sign up to set email alerts
|

Surface organization and composition of Euglena. II. Flagellar mastigonemes

Abstract: The surface of the Euglena flagellum is coated with about 30,000 fine filaments of two distinct types. The longer of these nontubular mastigonemes (about 3 micron) appear to be attached to the paraflagellar rod whereas the shorter nontubular mastigonemes (about 1.5 micron) are the centrifugally arranged portions of a larger complex, which consists of an attached unit parallel to and outside of the flagellar membrane. Units are arranged laternally in near registration and longitudinally overlap by one-half of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 28 publications
(22 reference statements)
1
30
0
Order By: Relevance
“…Some examples are; the large cell-body scales of prymnesiophyte algae (recently reviewed by Leadbeater 1994), the flagellar (Becker et al 1990;Becker and Melkonian 1992) and thecal scales (Becker et al 1989(Becker et al , 1995c of Tetraselmis striata, and the basket scales of Mesostigma viride (Domozych et al 1991). In addition, different types of flagellar hairs have been biochemically characterized: from Chlamydomonas reinhardii (Witman et al 1972;Monk et al 1983), Euglena gracilis (Bouck et al 1978;Rogalski and Bouck 1980) and Ochromonas (Kawano and Bouck 1984). In most of these studies only a few glycoproteins were found and, so far, the presence of disulfide bridges has not been investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Some examples are; the large cell-body scales of prymnesiophyte algae (recently reviewed by Leadbeater 1994), the flagellar (Becker et al 1990;Becker and Melkonian 1992) and thecal scales (Becker et al 1989(Becker et al , 1995c of Tetraselmis striata, and the basket scales of Mesostigma viride (Domozych et al 1991). In addition, different types of flagellar hairs have been biochemically characterized: from Chlamydomonas reinhardii (Witman et al 1972;Monk et al 1983), Euglena gracilis (Bouck et al 1978;Rogalski and Bouck 1980) and Ochromonas (Kawano and Bouck 1984). In most of these studies only a few glycoproteins were found and, so far, the presence of disulfide bridges has not been investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies (3) have revealed that treatment of whole flagella with low concentrations of detergents selectively extracts one of the two major glycoproteins and leaves the other major glycoprotein(s) (mastigonemes) in a particulate fraction . The following method therefore provided soluble extracts of the one flagellar glycoprotein with minimal disruption of the axoneme, membrane, and mastigonemes.…”
Section: Selective Solubilization Of a Nonmastigoneme Flagellar Giycomentioning
confidence: 99%
“…Dark grown culture after seven days was harvested by centrifugation (800 g for 5 min), washed twice with deionised water and once in HEPES buffer (10 mM, pH 7.0 HEPES/KOH, 25 mM KCl). The harvested cells were re-suspended in HEPES buffer and de-flagellated by the method of cold-shock [30] that required incubation on ice for 2 h and the collection of de-flagellated cells by centrifugation (800 g for 5 min).…”
Section: Methodsmentioning
confidence: 99%